Synthesis of Some New Metal Complexes of 5,6-O- Isopropylidene-2,3,-O,O Acetic Acid-L-Ascorbic Acid and Evaluation their Biological Activity - Sultan, J. S.; Mukhlus, A. A.; Musa, F. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Stable new derivative of L-ascorbic acid, 5,6-O-iso propylidene 2,3-O,O acetic acid-Lascorbic acid (L) was synthesized in good yield by the reaction of 5,6-O-isopropylidene-Lascorbic acid with chloroacetic acid in presence of potassium hydroxide. The new product (L) was characterized by 1H, 13Câ€“NMR, mass spectrum and fourier transform infrared (FTIR). The reaction of the ligand (L) with metal bivalent ion., M+2 = (Co, Ni, Cu, Cd, Hg, Mg, Ca, Pb) synthesized and characterized by FTIR, UV-Visible, Molar conductance, Atomic absorption and the molar ratio (Ni+2, Cd+2) complexes. Spectroscopic evidence showed that the binding of the M(II) ions with (L) are through the (Câ€“I=O) Lacton and O-2-CH2COOâ€“ as a bidentate manar resulting in a sixâ€“ coordinated metal ion; the values of ï¡, KF, ï„G were estimated for Cd+2, Ni+2 complexes and ï¢, B value, for Co+2, Ni+2 complexes were calculated too. The study of biological activity of the ligand (L) and (Cd+2, Cu+2, Ca+2) complexes showed various activities toward staphylococcus aureu and Escherichia coli, except Cacomplex didn’t show any effect